HEMATOLOGICAL AND BIOCHEMICAL PARAMETERS IN CLINICAL SPECTRUM OF INDIAN SICKLE CELL DISEASE PATIENTS - IPSITA DAS; DNYANESH AMLE; PRAFULLA KUMAR KHODIAR; HRISHIKESH MISHRA; PRADEEP KUMAR PATRA (International Journal of Pharma and Bio Sciences, 2016)
Sickle cell disease (SCD) is a hemoglobinopathy prevalent in Chhattisgarh and other states of central India. In Chhattisgarh, SCD patients and carriers comprise 9.35% of the population. Objective behind this study was to determine hematological and biochemical parameters along with serum electrolytes in SCD patients. Fifty subjects were included from each of four categories viz., SCD patients in steady state, in vaso-occlusive crisis state, SCD carriers and healthy controls. Hematological, biochemical parameters and serum electrolytes were measured. Statistical analysis was done to find significantly different parameters among four categories (P value ≤0.05). Hemoglobin, erythrocyte count, red cell distribution width, hematocrit, total leukocyte count, serum bilirubin, aspartate transaminase, alanine transaminase, alkaline phosphatase, serum sodium and potassium were found to be significantly different amongst four groups. Platelet count was decreased during vaso-occlusive crisis (VOC) though not significantly. Serum Sodium and potassium were significantly decreased during vaso-occlusive crisis. Implications of these findings were discussed.